FAKTOR-FAKTOR YANG MEMPENGARUHI CADANGAN DEVISA DI INDONESIA - Syifa Ma’rifatul Hidayah (Valuasi : Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2022)
Foreign exchange reserves are savings owned by the state for international trade transactions, maintaining monetary stability and paying foreign debts. The purpose of this study to determine the effect of exports, imports, GDP and exchange rates on Indonesia's foreign exchange reserves in 1990-2019. This study uses the ECM model which includes stationarity test, cointegration test, long-term test, short-term test, F test, t test, coefficient of determination test ( )  and classical assumption test. The test results show that the export variable has a significant positive effect on foreign exchange reserves, imports have a negative significant effect on foreign exchange reserves, while GDP and the exchange rate have no long or short term effect on foreign exchange reserves